Republic of Estonia : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2003)
Prudent macroeconomic policy, based on a balanced budget strategy and structural reforms, has successfully transformed Estonia into an open and flexible market economy and as a star performer among European Union accession countries. Executive Directors welcomed these developments and commended prudent fiscal policy, soundness of the financial sector, strong credit growth through reserve requirements, and good lending practices. They welcomed the effective mechanisms to combat money laundering and financing of terrorism, and efforts to promote data transparency and dissemination.